THE ACCOUNTING EXCHANGE. - Littleton, A. C. (The Accounting Review, 1944)
Abstract Professor Thomas W. Leland has been appointed as education director of American Institute of Accounts. According to the press, his work for the institute will include development of refresher courses sponsored by the institute and collegiate schools of accounting for members of the accountancy profession returning to their practice after war service. Included also in the educational program to be administered by Leland will be relations with state boards of examiners of states which have officially adopted the standard American Institute examination for certified public accountants. In this phase, Leland will work with the board of examiners of the institute. He will also be concerned with other educational activities of the organization. In expanding its service to the profession, the institute is making increasing use of staff comprising of various functional heads. A technical assistant is provided in normal times for each of several important research committees and a director of research is retained to coordinate the work.